RETRACTED: The attitude of uzbek scientists to the problem of developing perception and imagination of visual art works among schoolchildren - Ostonova Gulshod; Azimova Muhayyo; Tukhsanova Vilayat (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001